Breast reconstruction following nipple-sparing mastectomy: clinical outcomes and risk factors related complications. Issue 6 (2nd November 2017) - Laporta, Rosaria; Longo, Benedetto; Sorotos, Michail; Farcomeni, Alessio; Patti, Caterina; Mastrangeli, Maria Rosaria; Rubino, Corrado; Santanelli di Pompeo, Fabio
Abstract: Background: The aim of this study was to investigate clinical outcomes and risk factors related complications in patients who had undergone nipple-sparing mastectomy (NSM) followed by implant-based or autologous reconstruction. Methods: Between 2004–2014 a single-institution retrospective review was collected on NSMs reconstruction. Patient demographics, comorbidities, breast morphological factors, type and timing of radiotherapy, type of incision, reconstruction type and timing, implant volume and complications were collected. Results: A total of 288 patients had undergone 369 NSMs, 81 (28.1%) of which were bilateral while 207 (71.9%) unilateral. One-hundred mastectomies were performed for prophylactic purposes whereas 269 were therapeutics. Thirteen (4.5%) patients were active smokers, while 2 (0.7%) were diabetics. Fifty-five breasts (14.9%) were previously irradiated and average time elapsed between radiotherapy and NSM was 9-year, (range, 5–15 yrs). Total complication rate was 13.5% at mean follow-up of 47.98 months (range, 6–114 months). Partial-thickness and full-thickness mastectomy skin flap and NAC necrosis occurred in 39 (78%) and in 10 (20%) breasts, respectively. Previous radiotherapy and implant volume were significant predictors of complications (OR: 10.14, 95% CI: 3.99–27.01; OR × 100 g: 3.13, 95% CI: 1.64–6.33). Overall mastectomy type incision was not predictive of complications ( p  = .426). No association was observed between radiotherapy and mastectomy type access ( p  = .349). Conclusions: From our experience NSM followed by implant-based and autologous reconstruction had a relative high rate of complications comparable to previous reports. Despite this, it should be carefully offered to patients in whom potential risk factors are identified.